Yield loss in sunflower cultivars due to bird attack - Silva, Paulo Sérgio; Tomaz, Francisco Linco; Siqueira, Patrícia Liany; Silva, Paulo Igor; Lima, Levi Afonso (Revista Ciência Agronômica, 2018)
Bird attacks on the sunflower may hinder its exploitation in the Brazilian semi-arid region. The aim of this study was to evaluate the effects of different levels of protection (0, 33, 66 and 100%) of the capitula of eight sunflower cultivars, evaluated in randomized blocks with sub-divided plots and four replications. The cultivars were allocated in the plots and the levels of protection in the sub-plots, by covering the capitula with caps of non-woven fabric after physiological maturity. The most frequent bird species was the Paroaria dominicana. The Aguará 06 cultivar was the most productive and most tolerant to bird attack, followed by the Helio 250, CF 101 and Charrua cultivars. There was a positive correlation between yield loss (YL) due to birds and the flowering period, YL and the period for physiological maturity, YL and capitulum diameter, YL and stem diameter, YL and plant height, YL and the angle of the capitulum with the stem, and between YL and the distance of the capitulum from the ground. A negative correlation and the absence of correlation were seen between YL and the number of leaves, and between YL and distance of the capitulum to the stem respectively. The effects of protecting the capitula were similar for grain yield in the cultivars under test. Use of the caps was efficient, since an increase in the proportion of protected capitula determined an increase in grain yield, number of grains per capitulum and 1000-grain weight. These increases continued up to a certain proportion, after which there was a decrease in the three characteristics.